IMPLEMENTASI PRINSIP PRUDENTIAL BANKING DALAM PERBANKAN SYARIAH: ANALISIS YURIDIS TERHADAP PENERAPAN PRINSIP KEHATI-HATIAN DALAM MENJAGA STABILITAS DAN KEPERCAYAAN MASYARAKAT - Reillo Subaktio; Gallyn Ditya Manggala; Sheny Yulianty (An Nuqud Journal of Islamic Economics, 2026)
The development of the Islamic banking industry in Indonesia has shown a significant increase in line with the increasing public need for financial services based on sharia principles. Despite having different operational characteristics from conventional banking, Islamic banks still face various risks that can affect the health and sustainability of their business. Therefore, the application of prudential banking principle is a fundamental aspect in the implementation of Islamic banking activities. This research aims to analyze the concept, legal basis, implementation, and challenges of applying the prudential principle in Islamic banking in Indonesia. The research method used is normative legal research with legislative, conceptual, and analytical approaches. The results of the study show that the implementation of the prudential principle in Islamic banking is carried out through the implementation of comprehensive risk management, financing feasibility analysis, strengthening good corporate governance, applying the principle of knowing customers, fulfilling capital adequacy, and monitoring of sharia compliance. The application of these principles is not only aimed at protecting public funds, but also to maintain the stability of the national financial system and realize sharia goals in economic activities. However, its implementation still faces various challenges, including increasing financing risks, financial technology developments, limited human resources, and regulatory complexities that must be complied with simultaneously.